Thirty‐Year Risk of Cardiovascular Disease Events in Adolescents with Severe Obesity. Issue 3 (5th February 2020) - Ryder, Justin R.; Xu, Peixin; Inge, Thomas H.; Xie, Changchun; Jenkins, Todd M.; Hur, Chin; Lee, Minyi; Choi, Jin; Michalsky, Marc P.; Kelly, Aaron S.; Urbina, Elaine M.
Abstract : Objective: Quantifying risk for cardiovascular disease (CVD) events among adolescents is difficult owing to the long latent period between risk factor development and disease outcomes. This study examined the 30‐year CVD event risk among adolescents with severe obesity treated with and without metabolic and bariatric surgery (MBS), compared with youths with moderate obesity, overweight, or normal weight. Methods: Cross‐sectional and longitudinal comparisons of five frequency‐matched (age and diabetes status) groups were performed: normal weight ( n = 247), overweight ( n = 54), obesity ( n = 131), severe obesity without MBS ( n = 302), and severe obesity undergoing MBS ( n = 215). A 30‐year CVD event score developed by the Framingham Heart Study was the primary outcome. Data are mean (SD) with differences between time points for MBS examined using linear mixed models. Results: Preoperatively, the likelihood of CVD events was higher among adolescents undergoing MBS (7.9% [6.7%]) compared with adolescents with severe obesity not referred for MBS (5.5% [4.0%]), obesity (3.9% [3.0%]), overweight (3.1% [2.4%]), and normal weight (1.8% [0.8%]; all P < 0.001). At 1 year after MBS, event risk was significantly reduced (7.9% [6.7%] to 4.0% [3.4%], P < 0.0001) and was sustained for up to 5 years after MBS ( P < 0.0001, all years vs. baseline). Conclusions: Adolescents with severe obesity are at elevated risk for future CVD events. Following MBS, the predicted risk of CVD events was substantially and sustainably reduced.